Molecular basis for PICS-mediated piRNA biogenesis and cell division - Xiaoyang Wang (Nature Portfolio, 2021)
C. elegans piRNA biogenesis and chromosome segregation (PICS) complex is composed of TOFU-6, PICS-1, ERH-2, and two mutually exclusive factors PID-1 and TOST-1. By employing biochemical, structural, and cellular biology methods, the authors show that the PICS complex is an octamer consisting of two copies of each subunit, and functions in piRNA biogenesis and mitosis.